Agri-Science Faculty Perceptions of Communication Activities at Texas Tech University, a Non-Land-Grant Institution - Kelsi Opat; Erica Irlbeck; Kristyn Dickey (Journal of Applied Communications, 2021)
Due to the direct impact science has on society, it is important for scientists to communicate with the general public (Rose et al., 2020). There are various means of communication that scientists may choose to disseminate their research. Recently, Bowman et al. (2018) assessed how often Extension personnel at a land-grant institution used various communication skills, how important they perceived each skill to be, and how comfortable they were performing them. Land-grant institutions have different communication expectations for their faculty than those at non-land-grant institutions. Therefore, this study focused on the Use, Comfort, and Importance of communication skills according to faculty members at a non-land-grant university. Survey data were collected from 57 (N = 57) faculty members at Texas Tech University, a non-land-grant institution, within its College of Agricultural Sciences and Natural Resources. Average Use, Comfort, and Importance scores were calculated for each communication skill and categorized as high, average, or low. These scores indicated whether the faculty members at this non-land-grant institution had adopted each communication skill according to Rogers’ Innovation Diffusion Process.
Keywords: science communication; Innovation Diffusion Process; non-land-grant; communication activities; social media; communication training